Expatriation in Chinese MNEs in Africa: an agenda for research - Jackson, Terence; Horwitz, Frank Martin (Taylor and Francis, 2017)
Despite increasing Chinese MNE activity there is a paucity of studies and critical analysis of expatriate management in Emerging Market Multinational Enterprises (EMMNEs). We argue that Chinese firms’ expatriation policies and practices should be viewed in a different light to those of Western firms. We question whether Western modernization assumptions for emerging markets, often implicit within the international HRM literature, are appropriate when applied to Chinese MNEs. This has implications for the motivations of official Chinese policy regarding the presence of state MNEs in African countries, and individual Chinese MNE expatriation policies. Political-seeking motives may be moderated by an apparent disjuncture between Chinese official policy and individual firms’ operational practices. Some potential synergies between Chinese and African cultural values are moderated by a low importance placed on the knowledge transfer role of Chinese expatriates and by the impact of the relational nature of career development including expatriate selection and an apparent low emphasis on pre-departure training. The main contribution of this work is to inform future empirical research at organizational level by making explicit differences in Chinese MNE engagement in Africa to Western MNEs, how this may influence expatriate policy and practices, and why this may contribute a different perspective to the extant expatriation literature. This article provides a critical evaluation of the current literature, theory and research, and identifies an agenda for expatriation research in the African context
Keywords: Expatriation; Emerging market multinational enterprises; China in Africa; International HRM; Knowledge transfer; Modernization theory